Standardization and accuracy of millimeter endodontic rulers (Research, Society and Development, 2023)
Objective: To evaluate and compare the standardization and accuracy of millimeter endodontic rulers among three different brands available on the market, comparing their lengths with the standard measurement of the caliper. Methodology: This is a quantitative laboratory study where thirty rulers were selected and included in 3 groups of 10, according to the commercial brand: 1. Prism; 2. MK Life and 3. Maquira. In each ruler, the measurement of 15, 20, 25 and 30 mm was measured using an electronic digital caliper. As for standardization, the Student's t test was used (p < 0.05), whereas in relation to accuracy, the results were expressed through the average and average error of each group, thus comparing the results between the units of each group . Results: After the statistical analysis, the rulers produced by the brand Prisma and MK Life were standardized because they did not present significant differences (p > 0.05), in relation to accuracy they presented lower absolute mean errors, as they were closer to the nominal lengths , however, the Maquira ruler was the least standardized and accurate, according to the same tests analyzed. Conclusion: Prisma and MK Life endodontic rulers proved to be standardized and accurate. However, the Maquira brand endodontic rulers did not show standardization and accuracy.